Association between cardiopulmonary bypass duration and early major adverse cardiovascular events after surgical repair of supravalvular aortic stenosis - Simeng Zhang; Caiyi Wei; Bo Peng; Lizhi Lv; Fengbo Pei; Jianming Xia; Jun Yan; Jie Liu; Qiang Wang; Yi Shi (Frontiers in Cardiovascular Medicine)
BackgroundPatients who underwent surgical repair of supravalvular aortic stenosis (SVAS) are at high risk for postoperative major adverse cardiovascular events (MACE). This study aimed to investigate the association between cardiopulmonary bypass (CPB) duration and MACE occurring during postoperative hospitalization or within 30 days post-surgery.MethodsPatients who underwent surgical repair of SVAS from 2002 to 2019 at Beijing Fuwai Hospital and Yunnan Fuwai Hospital were included in this study. Patients were stratified into “CPB duration >2 h” and “CPB duration ≤2 h” groups based on intraoperative CPB duration. Various statistical methodologies were employed to investigate the association between CPB duration and early postoperative MACE, including multivariate adjustment, propensity score adjustment, propensity score matching, and logistic regression based on propensity score weighting.Results297 participants were included and 164 were finally matched. In the propensity score-matched cohort, CPB duration was positively associated with early postoperative MACE (odds ratio = 18.13; 95% confidence interval 2.33–140.86; P = 0.006). Consistent results were obtained in the Inverse probability of treatment-weighted, standardized mortality ratio-weighted, pairwise algorithmic-weighted, and overlap-weighted models.ConclusionPatients with CPB duration >2 h were at a higher risk of early postoperative MACE compared to those with CPB duration ≤2 h. This emphasized the significance of minimizing CPB exposure for the prognosis of patients with SVAS.